NAVIGATING THE ETHICAL CHALLENGES AND INNOVATIONS IN PERSONALIZED CONTENT RECOMMENDATIONS, DATA PRIVACY PROTECTION, AND CONSUMER TRUST WITHIN THE REALM OF AI-DRIVEN E-MARKETING STRATEGIES - Pupung Purnamasari; Simon Matakena; Muhammad Syafri; Nurussama; Syusantie Sylfia Sairdama (CV. Adiba Aisha Amira, 2024)
This research delved into the intricate ethical landscape that characterized AI- driven e-marketing. It began by outlining the significance of personalized content recommendations, elucidating their role in enhancing user engagement and conversion rates. While showcasing the benefits of AI-driven personalization, the study unveiled the ethical intricacies of the data collection and user profiling process. Concerns emerged, notably about data privacy, consent, and the potential formation of filter bubbles and echo chambers. Innovative solutions emerged in the form of transparent algorithms and robust user consent mechanisms to address these ethical quandaries. These mechanisms granted users greater control over their data and fostered transparency in content recommendation algorithms. Additionally, the study underscored the importance of consumer trust in e-marketing, emphasizing its pivotal role in brand loyalty and advocacy. Overall, this research offered a comprehensive understanding of the ethical challenges and solutions within AI-driven e-marketing, underscoring the industry's commitment to ethical practices while harnessing the potential of AI to provide personalized and engaging user experiences.